Kierkegaard's relations to Hegel reconsidered - Stewart, Jon 1961- (Cambridge University Press, 2003)
Jon Stewart's study is a major re-evaluation of the complex relations between the philosophies of Kierkegaard and Hegel. The standard view on the subject is that Kierkegaard defined himself as explicitly anti-Hegelian, indeed that he viewed Hegel's philosophy with disdain. Jon Stewart shows convincingly that Kierkegaard's criticism was not of Hegel but of a number of contemporary Danish Hegelians. Kierkegaard's own view of Hegel was in fact much more positive to the point where he was directly influenced by some of Hegel's work. Any scholar working in the tradition of Continental philosophy will find this an insightful and provocative book with implications for the subsequent history of philosophy in the twentieth century. The book will also appeal to scholars in religious studies and the history of ideas
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Kierkegaard, Søren / 1813-1855; Hegel, Georg Wilhelm Friedrich / 1770-1831; Hegel, Georg Wilhelm Friedrich -- 1770-1831; Kierkegaard, Søren -- 1813-1855; Rezeption; Hochschulschrift